2018
DOI: 10.2478/zireb-2018-0022
|View full text |Cite
|
Sign up to set email alerts
|

Do Croatian Companies Recognize Benefits of Integrated Reporting?

Abstract: Timely access to information and business transparency make the foundation for business success. Companies present their financial position and financial performance through the financial statements. As a financial information is not the only relevant factor of business value creation, presentation of non-financial information brings added value to different stakeholders. For the purpose of more transparent business operations and international comparability of the presented data, it is especially important th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In order to evaluate the effect of a formal obligation for certain companies to disclose non-financial information within their management report, annual report or other kind of reports, several studies have been observed in Croatia. Dečman and Rep (2018) conducted an empirical research on non-financial information disclosures on a sample of Croatian largest companies for FY 2016 (before the legislation amendments). The overall conclusion was that there was room for improvement of non-financial information disclosures since Croatian companies still did not fully recognize the benefits of integrated (financial and non-financial) reporting.…”
mentioning
confidence: 99%
“…In order to evaluate the effect of a formal obligation for certain companies to disclose non-financial information within their management report, annual report or other kind of reports, several studies have been observed in Croatia. Dečman and Rep (2018) conducted an empirical research on non-financial information disclosures on a sample of Croatian largest companies for FY 2016 (before the legislation amendments). The overall conclusion was that there was room for improvement of non-financial information disclosures since Croatian companies still did not fully recognize the benefits of integrated (financial and non-financial) reporting.…”
mentioning
confidence: 99%